2017
DOI: 10.1016/j.jallcom.2017.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Curie temperature and cooling efficiency in melt-extracted Gd50(Co69.25Fe4.25Si13B13.5)50 microwires

Abstract: We report enhancements of both Curie temperature and magnetic refrigerant capacity in Gd 50 (Co 69.25 Fe 4.25 Si 13 B 13.5) 50 microwires, which were fabricated by the melt-extraction method. For a field change of 5 T, the maximum magnetic entropy change (-ΔS M max), the refrigerant capacity (RC) and relative cooling power (RCP) reached high values of 6.56 J•kg-1 •K-1 , 625 J•kg-1 and 826 J•kg-1 , respectively. While the RC is similar to those of our previously reported GdAlCo microwires, a much broader workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In comparison with the table-like MCE in other alloys at analogous temperature ranges, such as Gd 55 Co 35 Mn 10 annealed at 600 K for 30 min (|∆S M | of 5.46 J•kg −1 •K −1 with a temperature range from 137 K to 180 K) [14] and fully crystallized Gd 55 Co 35 Ni 10 (620 K/30 min) ribbon (|∆S M | of 5.0 J•kg −1 •K −1 with a temperature range from 154 K to 214 K) [15], as listed in Table 1, the |∆S M | of the materials in this work are larger, but the temperature width of the plateau of |∆S M |-T is narrower. On another hand, when compared with single amorphous phase alloys, like Gd 75 (Fe 0.25 Co 0.75 ) 25 [24] and Gd 50 (Co 69.25 Fe 4.25 Si 13 B 13.5 ) 50 [25], the combined merits of larger or comparative |∆S M | and broader working temperature range can be observed in these Gd 60 Co 40 annealed samples. The MCE in a temperature range of 160-220 K can be used in the fields of space technology, medicine, biology, life sciences and more [14].…”
Section: Magnetocaloric Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In comparison with the table-like MCE in other alloys at analogous temperature ranges, such as Gd 55 Co 35 Mn 10 annealed at 600 K for 30 min (|∆S M | of 5.46 J•kg −1 •K −1 with a temperature range from 137 K to 180 K) [14] and fully crystallized Gd 55 Co 35 Ni 10 (620 K/30 min) ribbon (|∆S M | of 5.0 J•kg −1 •K −1 with a temperature range from 154 K to 214 K) [15], as listed in Table 1, the |∆S M | of the materials in this work are larger, but the temperature width of the plateau of |∆S M |-T is narrower. On another hand, when compared with single amorphous phase alloys, like Gd 75 (Fe 0.25 Co 0.75 ) 25 [24] and Gd 50 (Co 69.25 Fe 4.25 Si 13 B 13.5 ) 50 [25], the combined merits of larger or comparative |∆S M | and broader working temperature range can be observed in these Gd 60 Co 40 annealed samples. The MCE in a temperature range of 160-220 K can be used in the fields of space technology, medicine, biology, life sciences and more [14].…”
Section: Magnetocaloric Propertiesmentioning
confidence: 98%
“…Gd-TM (TM = Co, Fe, Ni, and Mn) amorphous alloys with near-room temperature MCE have attracted more attention in recent years. Generally, the broadened |∆S M |-T profile can be observed in these materials, owing to the highly disordered structure of amorphous systems, which smears out the magnetic transition [1,11,15,[17][18][19][20][21][22][23][24][25][26]. In-situ crystallization treatment of the amorphous ribbons is also utilized to obtain multi-phase magnetic refrigerant, such as crystallized Gd 55 Co 35 Ni 10 ribbon containing Gd 4 (Co, Ni) 3 and Gd 12 (Co, Ni) 7 phases, and partially crystallized Gd 55 Co 35 Mn 10 with precipitation of the Gd 3 Co-type and Gd 12 Co 7 -type phases in the amorphous matrix, both of them possess broadened table-like MCE [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Pure Gd, as the benchmark magnetic refrigerant, is commonly used in the active magnetic regenerator prototypes . In particular, Gd metal could be produced into different shapes due to its good mechanical properties, such as thin plate, sphere, and microwire, and it has been demonstrated that microwire is more desirable for realizing a higher cooling performance . However, Gd metal also has its disadvantages such as relatively low magnetic entropy change (Δ S M ), limited availability, and expensive price that hinder its large‐scale commercialization.…”
Section: Curie Temperature (Tc) Magnetic Entropy Change (δSm) Adiabmentioning
confidence: 99%
“…Although the technology has a wide application, many devices have relatively low Carnot efficiency (often less than 25%), and environmental concerns associated with leakage of the gaseous refrigerant. Increasingly, researchers are exploring alternative cooling technologies that may be more environmentally friendly and energy efficient that can be commercialized in the near future [1][2][3][4][5]. Magnetic refrigeration is a promising technology with potential advantages over conventional approaches, such as high energy efficiency, lack of a gaseous refrigerant, and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%